A novel suturing technique for natural tissue repair in cystocele treatment - Rahime Bedir Fındık; Melike Doğanay; Orhan Seyfi Aksakal; Zuhal Yapıcı Çoşkun; Jale Karakaya (BMC, 2024)
Abstract Background Recently, natural tissue repair has become popular in the treatment of pelvic organ prolapsed. In this study, we compared patients who underwent cystocele repair with the rug-weaving plication technique, a natural tissue repair method implemented since 2022 for anterior prolapse, with those treated using conventional colporrhaphy. Methods We retrospectively reviewed the data of 65 patients who underwent anterior vaginal wall repair with the rug-weaving plication technique (n = 33, Group 1) or conventional colporrhaphy (n = 32, Group 2). We recorded the patients' clinicodemographic and surgical data. At the 6-month postoperative follow-up, we assessed patients' complaints, degree of prolapse (using the simplified Pelvic Organ Prolapse Quantification system), and pelvic floor muscle strength (using the Modified Oxford Score). Anterior vaginal wall thickness was measured using transvaginal ultrasonography. We compared clinicodemographic and surgical data and postoperative outcomes between the two groups. Results The two groups were comparable in terms of age (p = 0.326), number of pregnancies (p = 0.307), number of parities (p = 0.555), preoperative anterior wall simplified Pelvic Organ Prolapse Quantification grade (p = 0.380), preoperative apical prolapse simplified Pelvic Organ Prolapse Quantification grade (p = 0.518), postoperative Modified Oxford Score (p = 0.857), operation time (p = 0.809), postoperative haemoglobin (p = 0.674), and amount of bleeding (p = 0.951). Compared with Group 2, Group 1 had significantly higher postoperative anterior vaginal wall thickness (p < 0.001) and significantly lower postoperative anterior wall simplified Pelvic Organ Prolapse Quantification grade (p < 0.001). Conclusions The rug-weaving plication technique may offer a viable alternative for cystocele repair without mesh, using natural tissue and potentially reducing mesh-related complications and recurrence rates. Clinical trial number NCT06410469 (03/05/2024).